La traducción de las expresiones militares estandarizadas en la películas del género bélico - Gordo Peleato, Rosario (Miscelánea: A Journal of English and American Studies, 2007)
When the average Spanish audience watches a dubbed war or military-content film, they are seldom aware of the lack of content synchrony often to be found in dubbed military jargon. This article focuses on the audiovisual translation of five different kinds of formulaic military expressions: standardized military expressions correctly translated according to their professional use, ‘pseudo-military’ standardized expressions, formulaic military expressions wrongly translated according to their professional use, the translation of ‘radio language’, and finally the translation of expressions of ‘military courtesy’. This research follows Relvance Theory (Sperber and Wison 1986, 1995) and specially Gutt’s (1991, 2000) investigation of translation phenomena from a relevance-theoretical perspective. Our findings are that although many military fomulaic expressions have been incorrectly translated —with respect to their professional use— the audiovisual translation of formulaic military expressions can be considered valid as long as the surface characteristics of both expressions (source and target) are similar, and the military connotations of the Spanish dubbed expressions sound ‘military enough’ to activate in the Spanish audience their encyclopedic knowledge on this particular issue. In such cases the audiovisual translation is based on a comparison of interpretations and not on the classical reproduction of words.